Judicial Review on Menchanical Rights of Musical Work (Case Study on of the Supreme Court Decree of the Republic of Indonesia No.018K/N/HaKi/2007, Concerning Royalty Payment by KCI in Against to WAMI) - Marissa Grace Haque; Vip Paramarta; Santi Rimadias; Kosasih Kosasih; Denok Sunarsi (Budapest International Research and Critics University, 2021)
A song creation is an object of copyrights in which Economic and Moral Rights are inherently attached to the song writer. Nonetheless, the problem then becomes crucial when the song writing comes into the recording process and produces an output of sound recordings and songs on his own work, the right which was originally attached only to the song writer but then it is shared to the Record Producers protected by the Mechanical Rights on the respective work of song recorded. It is, in fact, an opportunity for the song writers or Indonesian musicians to get back their Economic including Moral Rights which highly rely on the stand points of Songwriter towards YKCI as the collecting society and their Record Producers in pursuant to an understanding of the TRIPS Agreement in 1995 which obviously set out time period of protection term for Record Producers as the Neighboring Rights through the Mechanical Rights for the maximum duration of 50 years, since Indonesia has ratified the Berne Convention in 1997. As a result, exploitation of Economic right including Moral Rights of the song writer owned by the other parties that has occurred regrettably cannot be taken its benefit in a comprehensively balanced, equitable, and sustainable way by all stakeholders.